The case of taxing multinational corporations in Uganda: Do multinational corporations face lower effective tax rates and is there evidence for profit shifting? - Aliisa Koivisto; Nicholas Musoke; Dorothy Nakyambadde; Caroline Schimanski (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We study how large domestic firms and multinational corporations compare in their effective tax rates and whether there is evidence of profit shifting out of Uganda. Using administrative data from the Uganda Revenue Authority and regression analysis, we find that multinational corporations lower their corporate tax burden through two channels: lower effective tax rates and profit shifting. Multinational corporations pay lower effective tax rates, by approximately 20 percentage points, on their reported profits than large domestic corporations because of tax treaties and other benefits. However, they are also more likely to report losses than domestic firms. This is likely due to profit shifting, as we observe that the lower the tax rate in the country of the global owner, the lower the reported profit of the multinational corporation in Uganda. Developing countries are particularly vulnerable to profit shifting, given their limited fiscal capacity. Thus, the profit-shifting behaviour of multinational corporations creates substantial challenges for achieving sustainable development through strengthening domestic revenue mobilization. This study is among the first to provide evidence of profit shifting by multinational corporations in a low-income country setting.
Keywords: F63; H25; H26; O23; 330; multinational corporations; profit shifting